Netizen Aggressiveness Against Religious Content and Diversity on Facebook Media - Arnus, Sri Hadijah; Wahyudi, Firdaus; Cangara, Hafied; Hasrullah, Hasrullah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2022)
This research wants to analyze the forms of aggression carried out by netizens on social media in the form of videos, pictures, and memes containing blasphemy bringing the name of God, prophets, and religion, ethnicity, and class related to the blasphemy case committed by Basuki Cahaya Purnama (Ahok). This type of research is descriptive qualitative, the data collection method uses interviews with several netizens and discourse analysis related to content on social media. Based on the results of the research, it was found that there was content in videos, images, and memes that contained aggression directed at Ahok and his supporters and vice versa in the name of religion, ethnicity, and class. Aggressive behavior among netizens is due to the characteristics of social media which allow one to channel emotions safely and instantly because there is no need to meet face to face and eliminate the pressures caused by face to face communication. The most sensitive issues to be used as fuel that is very effective in carrying out aggression on social media are issues related to religion and ethnic and ethnic differences. improve online media literacy skills among netizens who use social media, through formal education and non-formal forums and support from various parties. This research is expected to contribute to minimizing polarization in society due to differences in religion and culture, especially ahead of the 2024 election.